The climate response of the Indo‐Pacific warm pool to glacial sea level. (30th June 2016) - Di Nezio, Pedro N.; Timmermann, Axel; Tierney, Jessica E.; Jin, Fei‐Fei; Otto‐Bliesner, Bette; Rosenbloom, Nan; Mapes, Brian; Neale, Rich; Ivanovic, Ruza F.; Montenegro, Alvaro
Abstract: Growing climate proxy evidence suggests that changes in sea level are important drivers of tropical climate change on glacial‐interglacial timescales. These paleodata suggest that rainfall patterns over the Indo‐Pacific warm pool (IPWP) are highly sensitive to the landmass configuration of the Maritime Continent and that lowered sea level contributed to large‐scale drying during the Last Glacial Maximum (LGM, approximately 21, 000 years B.P.). Using the Community Earth System Model Version 1.2 (CESM1), we investigate the mechanisms by which lowered sea level influenced the climate of the IPWP during the LGM. The CESM1 simulations show that, in agreement with previous hypotheses, changes in atmospheric circulation are initiated by the exposure of the Sunda and Sahul shelves. Ocean dynamical processes amplify the changes in atmospheric circulation by increasing the east‐west sea surface temperature (SST) gradient along the equatorial Indian Ocean. The coupled mechanism driving this response is akin to the Bjerknes feedback and results in a large‐scale climatic reorganization over the Indian Ocean with impacts extending from east Africa to the western tropical Pacific. Unlike exposure of the Sunda shelf, exposure of Sahul shelf and the associated changes in surface albedo play a key role because of the positive feedback. This mechanism could explain the pattern of dry (wet) eastern (western) Indian Ocean identified in climate proxies and LGM simulations. However, this response also requires a strengthened SST gradient along the equatorial Indian Ocean, a pattern that is not evident in marine paleoreconstructions. Strategies to resolve this issue are discussed. Key Points: Shelf exposure is the main mechanism whereby glacial changes in sea level influence warm pool climate The response is initiated by surface cooling over the Sahul shelf caused by the increased albedo of land relative to ocean conditions Coupled ocean‐atmosphere dynamics akin to the Bjerknes feedback amplify the response